The island of Java : sejarah tanah Jawa / John Joseph Stockdale ; penerjemah, Ira Puspitorini, An Ismanto - STOCKDALE, John Joseph; Ira Puspitorini; An Ismanto (Indoliterasi, 2014)
xiii, 446 hlm. ; 20 cm.